Knowledge, attitude, perceived effectiveness and self-practice of complementary and alternative medicine: a cross-sectional comparison between medical and non-medical students of Bangladesh - Mohammad Azmain Iktidar; Sreshtha Chowdhury; Simanta Roy; Mowshomi Mannan Liza; Sharmin Akter; A. M. Khairul Islam; Sefat Alam Pranto; Sristi Chowdhury; Md Asikur Rahman; Chowdhury Shama Binte Shafiul; Dipa Dev; Syed Md Sayeem Tanvir; et al. (BMC Complementary Medicine and Therapies, 2022)
Abstract Background Bangladesh’s population commonly utilizes Complementary and alternative medicine (CAM) to treat their health issues. Despite the increasing interest in CAM, it has been excluded from conventional medical training in Bangladesh for many years. Therefore, this study assessed and compared the knowledge level, attitude, perceived effectiveness, and self-practice of CAM among undergraduate students of Bangladesh. Methods This cross-sectional group comparison study was conducted among undergraduate (both medical and non-medical) students of Bangladesh between November and December 2021. Data was collected using a self-reported pretested semi-structured online questionnaire. The questionnaire contained questions regarding background information, knowledge regarding CAM, source of CAM knowledge, attitude towards CAM, interest in attaining CAM knowledge, perceived effectiveness of CAM, perceived adverse effects of CAM, self-practice of CAM, and whether would they refer CAM to others. A total of 576 students responded and the data gathered allowed for the following: (1) an overview of the study groups, (2) respondents’ general perception and knowledge regarding CAM, and (3) a comparison of respondents’ CAM knowledge, general perception, and usage by area of study. Data were analyzed using STATA (v.16) and descriptive statistics, Pearson’s chi-square test, and Mann-Whitney U test were performed. Results A total of 329 medical students and 247 non-medical students participated in the study. The mean age of the participants was 21.57 ± 1.8 years and 56.2% of them were male. The most known CAM among medical (M) students was homeopathy (44.6%) and among non-medical (NM) students were herbal medicine (45.7%). Non-medical students had significantly better knowledge about nine out of twelve CAM modalities included in the study, and no significant differences were present for the rest of the modalities. Medical (81.1%) and non-medical students (86.2%) perceived traditional Chinese medicine and homeopathy to be the most effective respectively. “Incorporating CAM with conventional medicine would result in increased patient satisfaction” showed the most statistically significant (p = 0.0002) difference among both groups. Yoga was the most often practiced modality among medical students and homeopathy among non-medical students. Conclusion Medical students have a lacking of knowledge and a positive attitude towards CAM, despite its very common practice among the people of Bangladesh. Therefore, emphasis should be put on the inclusion of CAM modules in medical training.